Use of Small Cetaceans as Bait in Small-Scale Fisheries in Peru - Campbell, Elizabeth; Pasara-Polack, Andrea; Mangel, Jeffrey C.; Alfaro-Shigueto, Joanna (Frontiers in Marine Science, 2020)
The use of small cetaceans as bait is a practice that has been reported worldwide, affecting the conservation status of vulnerable species. In Peru specifically, it has been documented since at least the late 1990s. Here we document the various contemporary uses of small cetaceans, including targeted capture for subsequent use as fishing bait. We designed a survey addressing fishery characteristics, bycatch and the use as bait of small cetaceans, and the history of these practice. We surveyed 147 fishers based in the four Peruvian ports of Paita, Salaverry, Pucusana and Ilo and held in-depth interviews with 12 fishers from Salaverry and Pucusana. Results from our surveys show that the majority of fishers have had small cetacean bycatch while fishing and that bycaught individuals in gillnets are commonly found dead (Salaverry: 100% of fishers, Pucusana: 58%) whereas in longlines small cetaceans are found alive (Paita: 74%, Ilo: 53%). We found that the use of dolphins as bait is still common in both gillnet and longline shark fisheries along the coast of Peru and that it is more frequent in northern ports. Gillnet fishers reported using one to four dolphins as bait per trip (10-15 sets) from bycatch events and discarding the rest if they have excessive bycatch, while longline fishers reported using 10 to 20 dolphins per fishing trip from either direct take by harpooning or the exchange of carcasses from gillnet vessels. Bycatch and use as bait mainly affects four species, the dusky, bottlenose and common dolphins and the Burmeister's porpoise. We identified three drivers of the use of dolphins as bait: effectiveness, availability and cost. These factors will have to be addressed in parallel if this practice is to be reduced. We recommend combining legislative and community-led strategies to reduce bait use and thus further the conservation of small cetacean populations in the southeastern Pacific Ocean.